Human Plasmacytoid Dendritic Cells Elicited Different Responses after Infection with Pathogenic and Nonpathogenic Junin Virus Strains - Negrotto, Soledad (2015)
The Junín virus (JUNV) arenavirus is the etiologic agent of Argentina Haemorrhagic Fever (AHF). We characterised the JUNV infection of human peripheral blood-derived plasmacytoid dendritic cells (hpDC), demonstrating that hpDC are susceptible to infection by the C#1 strain (attenuated), and even more, by the P (virulent) JUNV strain. However, hpDC elicited different responses in terms of viability, activation, maturation, and cytokine expressions after infection with both JUNV strains.